Dimensionality and reliability of the determinants of reverse mortgage use intention - Mohammed, Mohammed Ishaq; Sulaiman, Noralfishah; Adamu, Dahiru (Path of Science, 2018)
The decision to use reverse mortgage is influenced by a myriad of factors among which some are behaviourally related. Identification and validation of these behavioural factors are necessary to be able to objectively explain their interrelationships and effect on individual’s decision to use the product in the future. This paper reports a pilot survey result that aimed at validating a questionnaire designed specifically to collect data on the behavioural factors that might likely influence individual’s intention to use reverse mortgage in the future. Using a convenient sampling strategy, a total number of 102 sampled respondents were used in the study. The data were analyzed with the aid of the Statistical Package for the Social Sciences (SPSS) version 23 where a factor analysis and reliability analyses were conducted. The result revealed that out of the 53 items that originally formed the questionnaire items, only 41 were retained. A total of 10 components emerged from the data which were named in accordance with their underlying constructs. All the factor loadings in reported satisfied the acceptable threshold of .50. The reliabilities of the items and the respective scales were also within the acceptable range of .70. It was therefore concluded that the questionnaire was reliable and can be used for the purpose to which is was designed for